If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+(21+x)+(-23+2x)=690
We simplify the equation to the form, which is simple to understand
x+(21+x)+(-23+2x)=690
Remove unnecessary parentheses
+x+21+x+(-23+2x+)=+690
Remove unnecessary parentheses
+x+21+x-23+2x=+690
We move all terms containing x to the left and all other terms to the right.
+1x+1x+2x=+690-21+23
We simplify left and right side of the equation.
+4x=+692
We divide both sides of the equation by 4 to get x.
x=173
| 25-13x=-14 | | 5x-7x=-16 | | 6A+9B=-15 | | 4x^7y^5+12x^5y^4+20xy=0 | | 6A+9(6)=15 | | 2(7-x)=3(x+1) | | x^4-x^3-72x^2=0 | | 3u+16=52 | | X^2+19x+60=0 | | 7.36=6.28*x | | 11(t-6)+3t=7(2t+4)-13 | | 6x+4+x=3+3x+5 | | 7.18=23.14r | | 3+8=17 | | -3=8 | | x-3=5x+13 | | 5+x(x+2)=495 | | Y=2x^2+2x-3 | | 4/13=16 | | Y=2x*2+2x-3 | | (x+2)(x+5)=495 | | r+31=20 | | 10x+2=7x-8 | | 9x^2+16x^2=400 | | 2x^3+3*x^2+4x+5=0 | | x^4+2x^3+3*x^2+4x+5=0 | | 2x-100+x*x=10 | | u+17.5=35 | | 12(t-6)+6t=6(3t+3)-12 | | 3x-2(2-x)=6-x-10 | | 6x-6=5x+11 | | 6(-x-5)=-4(x-3)-x |